Perlindungan Konsumen Pelanggan Indihome Terhadap Kebocoran Data Pribadi - Indah Ipa; Theresia Louize Pesulima; Ronald Fadly Sopamena (Faculty of Law Universitas Pattimura, 2023)
Problems related to personal data leakage that have occurred in Indonesia, one of which is the leakage of personal data of IndiHome customers that are traded on internet sites that can be reached by anyone. The leakage of personal data has indirectly deprived human rights which are very detrimental to the human point of view. Protecting consumer rights is an obligation of business actors as regulated in article 4 paragraph 5 of Law No. 8 of 1999 concerning Protection of Consumers. This type of research is Normative Juridical, or literature research because this research is carried out or aimed only at written regulations or primary, secondary and tertiary legal materials, the data collection method used is literature study and document study and data analysis is carried out normatively and comprehensively. The results of this study, show that the form of legal protection for IndiHome customer consumers who experience personal data leakage can be done in the form of preventive legal protection (prevention) providing opportunities for legal subjects to raise objections or opinions before the government decision gets a definitive form and Repressive legal protection (coercion) is legal protection that leads to dispute resolution. Legal remedies of IndiHome consumers who were harmed due to negligence on the part of PT. Telecommunications as Electronic System Operators that cause leakage of personal data can file a lawsuit based on Unlawful Acts stipulated in Article 1365 and Article 1366 of the Civil Code.